Arsenic (III) detection with underpotential deposition and anodic stripping voltammetry - Zhang, Y; Li, D; Compton, RG (Wiley, 2021)
We report a stripping voltammetric method for the detection of aqueous As(III) using a Pt macroelectrode or a Pt nanoparticle-modified glassy carbon electrode (GCE) which, novelly, is based on the underpotential deposition of As atoms. The method consists of a pre-concentration reductive step to accumulate As ad-atoms onto Pt, followed by linear sweep voltammetry (LSV). It is shown that the stripping peak of As ad-atoms improves the response at low concentrations of As(III) as compared to analogous measurements using the deposition of bulk As. No interference was seen from Cu(II) at realistic concentrations although high concentrations of chloride inhibited the deposition of the ad-atoms. A linear response was found for the concentration range 0.05 to 1 μM As(III) at both types of electrode with a visually clear signal recorded at 0.05 μM (4 ppb), suggesting that this method has practical value noting the WHO limit of 0.13 μM (10 ppb) for safe drinking water.